An OBE-based e-module integrated with prophetic values: Enhancing statistical understanding, engagement, and character development - Vahlia, Ira; Sholiha, Sangidatus; Suprihatin, Siti; Utami Dewi, Wardhani (Jurnal Inovasi Teknologi Pendidikan, 2026)
Many students struggle to understand abstract concepts in Statistics because of limited contextual and interactive learning resources that connect theory to practice. Moreover, there is a lack of e-modules integrating prophetic values to support the vision of Universitas Muhammadiyah Metro. However, existing studies have not sufficiently integrated OBE with prophetic values in digital learning media for statistics, indicating a clear research gap. This study aims to develop an OBE-based e-module integrated with prophetic values for Statistics courses. The research employed an R&D method using the ADDIE model (analysis, design, development, implementation, and evaluation). The subjects were students of the Economic Education Study Program. Data were collected through interviews, expert validation and student response questionnaires, and analysed using descriptive quantitative and qualitative techniques. The results show that the e-module is highly valid (91.6%) and very practical (mean score = 4.3/5). Learning outcomes improved from an average of 62.5 to 83.7 (p < 0.05), indicating positive learning gains. This study provides contextual and methodological contributions by integrating OBE principles with prophetic values in digital learning design, and theoretical contributions in linking cognitive and character development in statistics learning. Future research should involve larger samples and longer implementation periods to assess affective outcomes better.